Schiller Wearing a Mask: The Literature of German-Speaking Countries vs. the sars-cov-2 Pandemic - Okoński, Krzysztof (Porównania, 2021)
Interventions of writers during a political transformation or crisis have a long history in the German-speaking countries. However, the sars-cov-2 pandemic has changed previous practices of civic engagement and literary reflection on contemporary problems. The authors are facing not only threats to their own material existence but they also facing the need to find new ways of communicating with their readers and are confronted with the growing radicalism and hostility against the elites. Based on selected press and radio materials, this article discusses such issues as the reorganization of literary life in Germany, Austria, Switzerland and Liechtenstein, writers’ responses to lockdown restrictions, literary images of the pandemic, polarization of the society, and the instrumentalization of literary and historical motifs by anti-Covid movements.